Origins, genetic structure, and systematics of the narrow endemic peatmosses (Sphagnum): S. guwassanense and S. triseriporum (Sphagnaceae)1. Issue 6 (1st June 2013) - Shaw, A. Jonathan; Shaw, Blanka; Johnson, Matthew G.; Higuchi, Masanobu; Arikawa, Tomotsugu; Ueno, Takeshi; Devos, Nicolas
Abstract : Premise of the study: Sphagnum dominates vast expanses of wetland habitats throughout the northern hemisphere and species delimitation within the genus is important because floristic changes associated with a warming global climate may have measureable impacts on large‐scale ecological processes. Most northern hemisphere peatmoss species ( Sphagnum ) have circumboreal ranges, but the Japanese species generally known as S. calymmatophyllum is endemic to Honshu Island. This prompted a population genetic and phylogenetic analysis to resolve the origin(s), population structure, and phylogenetic relationships of this morphologically variable species. Methods: Sixty plants collected from Mt. Gassan and Mt. Hakkoda were genotyped for 12 microsatellite loci. Two plastid loci and three anonymous nuclear loci were sequenced in a subset of the plants, plus representatives from 10 closely related species. Key results: Gametophytes exhibited fixed or nearly fixed heterozygosity at 9–10 of the 12 microsatellite loci. Two genetic groups were resolved by the microsatellite data, individuals showed no evidence of admixture, and the two groups of plants differ in morphology. They are heterozygous for different sets of alleles. The two taxa share plastid DNA sequences with two species that are common in Alaska. Conclusions: Two taxa were distinguished: S. guwassanense and S. triseriporum . Both are allopolyploids; they originated independently from different but closely related progenitors. The maternal progenitor was likely either S. orientale or S. inexspectatum . The two allopolyploid taxa are heterozygous for (different) private microsatellite alleles, and one progenitor could be extinct.